Przeobrażenia czytelnika modelowego i przesunięcia tłumaczeniowe - Wilkos, Aleksandra (Studia Europaea Gnesnensia, 2016)
The aim of this publication is to analyze the transformation of the Model Reader and translation shifts, using the example of three selected post-colonial pieces of writing, in Polish translation from Portuguese. An analysis of the shifts enables one to observe changes occurring between the Model Reader of the original and the Model Reader of the output text.